(untitled) (Journal of Economic Research & Business Administration, 2015)
Working out the totals, it is possible to assert that work on the exposure of points of management connection by investment activity, budgetary management, administrative and book-keeping account, formalization of these intercommunications and realization of them in single CAS of administrative account allow to provide monitoring of investment activity and realization of complete cycle of management in regard to investments, converting from their "black box" in the clear and controlled object of activity.